Degradation of high density polyethylene containing manganese carboxylates as pro-degradant additives under artificial and natural weathering - Maryudi, M. (2012)
The tremendous utilization of synthetic plastics over last decades has led to environmental problems due to lack of degradability of plastics.The degradability issue has resulted in development of degradable plastics which degrade faster.This study deals with utilization of manganese carboxylates (i.e.manganese laurate,manganese palmitate and manganese stearate) on enhancing degradation of high density polyethylene (HDPE).Initially, manganese carboxylates were synthesized through two-steps reactions:(i) sodium carboxylates synthesis by reacting sodium hydroxide and carboxylic acids,(ii) manganese carboxylates synthesis by reacting manganese chloride and sodium carboxylates. Characterization of manganese carboxylates was then carried out.Incorporation of manganese carboxylates up to 1% (w/w) into HDPE resin was carried out using twin screw extruder followed by injection molding to produce specimens.Thermal treatment was performed at 70°C for maximum duration of 1000 hours to examine the degradation of pure HDPE and HDPE containing manganese carboxylates.Accelerated weathering was conducted up to 1000 hours combining thermal and UV exposure.Natural weathering was carried out for 24 weeks under weather conditions of Gambang,Malaysia.Analyses of tensile strength,elongation at break, FTIR spectra,average molecular weight,melt flow index (MFI),thermogravimetry (TG),differential scanning calorimetry (DSC),X-ray diffraction (XRD),and scanning electron microscopy (SEM) were carried out to asses the changes during treatments. Results have revealed that all manganese carboxylates have demonstrated adequate thermal stability.Their melting temperatures are in range of 108-117°C.Manganese stearate has shown the highest thermal stability and melting point among manganese carboxylates synthesized.Thermal treatment has led to thermo-oxidative degradation of HDPE.Manganese carboxylates have significantly played a role in enhancing degradation of HDPE.The degradation increased by increasing amount of manganese carboxylates.During accelerated weathering,the degradation took place more rapidly than during thermal treatment,particularly for HDPE containing manganese carboxylates.Photo-degradation and thermo-oxidative degradation took place simultaneously during accelerated weathering and allowed dramatic reductions of essential properties.Natural weathering has given similar effects with accelerated weathering.Manganese carboxylates has also shown the capabilities on enhancing degradation of HDPE in natural environment.Manganese stearate has shown a slightly greater effect in enhancing degradation of HDPE than manganese laurate and manganese palmitate during all treatments.Pure HDPE lost its elongation at break about 16 %; 65 % and 64 %,whereas HDPE containing 1% manganese stearate lost its elongation at break about 62 %; 96 % and 95 % for thermal treatment;accelerated weathering and natural weathering respectively.Tensile strength and tensile modulus also decreased proportionally with the decrease of elongation at break.Other properties have also been found to decrease including average molecular weight,thermal stability,and melting point.The MFI,carbonyl index and crystallinity were found to increase after all treatments. Generally,manganese carboxylates have demonstrated the capabilities on enhancing degradation of HDPE under all modes of treatments.